Solid Pseudo Papillary Neoplasm of the Pancreas (Frantz Tumor) in a 19-Year-Old Female: A Case Report - Jane Racheal Ayikoru; Phiona Eyotaru; Kirabo Iga; Vianney Kweyamba (International Journal of Health Sciences, 2026)
We report the case of a 19-year-old female who presented with a one-month history of epigastric pain, nausea and occasional vomiting. Contrast-enhanced computed tomography demonstrated a characteristic solid-cystic mass in the pancreatic head suggestive of solid pseudo papillary neoplasm (SPN) of the pancreas. The patient underwent open pancreatico-duodenectomy (Whipple procedure). Histopathology confirmed a low-grade SPN with clear margins. Postoperative complications, including pancreatic fistula, acute pancreatitis and pleural effusion, were successfully managed. This case illustrates that complete surgical resection remains curative for SPN, with manageable complications and excellent long-term survival.